My Understanding of Manuj Babu and his Art - Subedi, Abhi (SIRJANĀ – A Journal Of Arts and Art Education, 2018)
Manuj Babu Mishra (1936-2018) was a modern artist who is mainly known for his paintings and his drawings. Nepali art critic Narayan Bahadur Singh as early as 1976 mentioned about his multiple skills in art. But Mishra was also one of those painters who ushered in an era of modern consciousness shared equally by painters and poets. His contemporaries some of whom are still painting though on a smaller scale, made experiments with their arts in modernist style. An era of distorting forms, breaking the fine figurality and using flatness by shunning the illusion of three dimensional shapes rather than representative forms was seen in Nepali modernist paintings too. Manuj Babu Mishra adopted a method of using figurality in paintings that used semi surrealistic and abstract paintings. Mishra was trained in Dhaka of the then East Pakistan in the late sixties of the last century. Despite his political statements occasionally, he was basically an artist. He was a peaceful man behind the hurricanes of hard times he created. He was also a portraitist who believed that the portrait of a person is also the portrait of the world outside him or her. He had said that to me when he was drawing my portrait.